Subwavelength and Nanometer Diameter Optical Fibers - Tong, Limin; Sumetsky, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Subwavelength and Nanometer Diameter Optical Fibers provides a comprehensive and up-to-date coverage of research on nanoscale optical fibers including the basic physics and engineering aspects of the fabrication, properties and applications. The book discusses optical micro/nanofibers that represent a perfect fusion of optical fibers and nanotechnology on subwavelength scale and covers a broad range of topics in modern optical engineering, photonics and nanotechnology spanning from fiber optics, near-field optics, nonlinear optics, atom optics to nanofabrication and microphotonic components/devices. It is intended for researchers and graduate students in the fields of photonics, nanotechnology, optical engineering and materials science. Dr. Limin Tong is a professor at Department of Optical Engineering and State Key Laboratory of Modern Optical Instrumentation of Zhejiang University, China; Dr. Michael Sumetsky is a researcher at OFS Laboratories, USA.
Optical Waveguiding Properties of MNFs: Theory and Numerical Simulations -- Fabrication of MNFs -- Properties of MNFs: Experimental Investigations -- MNF-based Photonic Components and Devices -- Micro/nanofiber Optical Sensors -- More Applications.
Keywords: Engineering; Microwaves; Optical materials; Nanotechnology; Engineering; Microwaves, RF and Optical Engineering; Nanotechnology; Optics, Optoelectronics, Plasmonics and Optical Devices; Optical and Electronic Materials; Laser Technology, Photonics